2016
DOI: 10.3892/etm.2016.3625
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers combined with uterine artery Doppler in prediction of preeclampsia

Abstract: First-trimester screening may be a major advantage over a second-trimester approach since it opens prospects for early and more efficient interventions. The aim of the current study was to evaluate whether the measurement of maternal serum inhibin A, activin A and placental growth factor (PlGF) at three to four months gestation with the second-trimester uterine artery pulsatility index (PI) are useful in predicting preeclampsia in a group of nulliparous women. All the patients also underwent uterine artery Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Placenta growth factor (PlGF) is a marker of angiogenesis that can increase the detection rate of pre‐eclampsia when combined with other variables for screening . Nonetheless, the efficacy of PlGF and its optimum cutoff level have not been studied in low‐risk Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Placenta growth factor (PlGF) is a marker of angiogenesis that can increase the detection rate of pre‐eclampsia when combined with other variables for screening . Nonetheless, the efficacy of PlGF and its optimum cutoff level have not been studied in low‐risk Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chang et al(25) found the predictive model consisting of mean arterial pressure (MAP), UAPI and serum biomarkers showed predictive value for the early (11-13 weeks GA) diagnosis of early PE with fetal growth retardation of 73.2%.Moreover, Tsiakkas et al(26) reported that combined screening by maternal factors, MAP, UAPI and biomarkers predicted 98% of preterm-PE and 49% of term-PE, at a false-positive rate of 5%. Also, Li et al(27) reported that in pregnancies that developed PE, the UAPI was increased and a combination of biomarkers and UAPI gave an AUC of 0.915 with 91% sensitivity at 82% specificity.The reported positive significant correlation between high SBP, a diagnostic criterion for PE and at 12-w GA high BMI and serum ADMA levels and the negative significant correlation between high SBP and serum NO and E2 levels spot light on a possible relationship between disturbed NO/ADMA axis, obesity, disturbed sex hormonal milieu on one side and the development of PE on the other side.…”
mentioning
confidence: 99%
“…Li et al (26) demonstrated that UtA PI at early secondtrimester was increased in pregnancies that developed PE (1.61±0.047 vs. 1.02±0.049, p<0.001). In contrast, the level of PlGF was decreased in preeclamptic group compared to controls (0.69±0.23 vs. 1.00±0.26, p<0.001) (26).…”
Section: Discussionmentioning
confidence: 69%